(untitled) (Journal of Enam Medical College, 2015)
Background: Jaundice is very common in the neonatal period of life. Although it is not a major cause of mortality, it is an important cause of morbidity. So, assessment of the causes and risk factors of neonatal jaundice is very important. Objectives: The objectives of the study were to find out the causes of jaundice, its clinical features, evaluation of the outcome of current management strategy and complications encountered by the participating subjects following treatment. Materials and Methods: This prospective study was conducted in the Neonatal Unit of Rangpur Medical College Hospital (RpMCH) during July to December 2006. A total of 100 neonates having jaundice on admission or who developed jaundice following admission were included in the study. A number of investigations were done for the purpose of assessment of neonates and their icteric condition. The test statistics used to analyse the data were descriptive statistics, Chi-square (?2) and correlation tests. Results: In the present study the median age of the jaundiced newborns on admission was 5 days, while the median age of appearance of jaundice was 3.5 days. Most of the newborns exhibited jaundice 24 hours after birth and peaked by 34 days. Majority of the subjects (77%) had pathological jaundice and only 23% had physiological jaundice. This study shows septicemia was in 28% cases followed by asphyxia (20%), prematurity (18%), Rh incompatibility (15%), IUGR (11%) etc. Half of the newborns (51%) had serum bilirubin (indirect) >10 mg/dL. Gestational age and serum bilirubin was found to exhibit a negative correlation. Preterm babies also tend to develop severe to very severe jaundice more than their term counterparts (p<0.001). Birth weight was also found to bear a negative correlation with serum bilirubin. Low birth weight (LBW) babies also had a significantly higher tendency to develop severe to very severe jaundice (p<0.001). Of the 77 patients who were treated, about 64% received phototherapy, 61% received antibiotics and very few (5.2%) received exchange transfusion. Majority of the patients developed some sorts of complications. The predominant complications of phototherapy were irritability (40.8%) followed by skin rashes (26.5%), loose motion (20.4%) and dehydration (16.3%). Very few newborns (4%) had hyperthermia. All four babies who received exchange transfusion suffered from hypovolaemia, one developed hypoglycaemia and one exhibited anaemia. Conclusion: Neonatal jaundice is a leading cause of hospitalisation in the first few weeks of life throughout the world. Though management of unconjugated hyperbilirubinaemia in newborns has undergone changes based on emerging evidences, phototherapy and exchange blood transfusion are still the most commonly used effective modalities for lowering serum bilirubin level. J Enam Med Col 2015; 5(2): 104-109